The Effect of Leadership and Work Environment on Job Satisfaction Through Motivation as a Mediation Variables in PT. Trinitan Plastic Industries - Aisyaturrido; Imam Wibowo; Nuridin. SE. MM (The Institute of Academic Research and Publication (IARP), 2021)
This study aims to determine the direct influence of leadership and work environment on job satisfaction, to know the direct influence of motivation on job satisfaction, to know the direct influence of leadership and work environment on motivation, and to know the influence of leadership and work environment on job satisfaction through motivation. This study using the path analysis method and the sample of researchers using a random sample of 62 employees. The results showed that leadership and work environment directly influence job satisfaction. Motivation directly affects job satisfaction. Directly leadership and work environment affect motivation, and leadership and work environment affect job satisfaction through motivation.